Local structural unfolding at the edge-strands of beta sheets is the molecular basis for instability and aggregation of G85R and G93A mutants of superoxide dismutase 1. Issue 3 (11th February 2020) - Kumar Ghosh, Debasish; Nanaji Shrikondawar, Akshaykumar; Ranjan, Akash
Abstract: Dynamic nature of structural segments is a key modulator of protein's intrinsic stability. Mutants of superoxide dismutase 1 (SOD1) protein, like SOD1 G85R and SOD1 G93A, adopt misfolded states that undergo aggregation in motor neuron cells. In this study, we had used correlative computational studies to investigate the temporal flux of structural alterations in SOD1 G85R and SOD1 G93A that increased the instability and aggregation tendency of these proteins. Molecular dynamics simulation studies showed that the G85R and G93A mutations caused localized transitions of the edge-strands of beta sheets to disordered structures near the mutation regions. Though this structural perturbation did not alter the conformation of the catalytic zinc and copper binding residues, it could dislocate the electrostatic loop of SOD1 G85R . This had rendered the electrostatic loop of SOD1 G85R to be incapable of guiding the substrate to the catalytic cleft. The beta sheet-to-disorder transitions near the mutations had caused the induction of steric clashes in the edge-strand residues, resulting in the loss of several intra-molecular interactions in the mutant SOD1 proteins. These had effected in local structural destabilization and increased aggregation potential in SOD1 G85R and SOD1 G93A . Mutant SOD1 proteins adopted energetically less favorable states, with some changes in the residue-level conformation entropy and solvent-exposed surfaces of the mutation neighboring residues. Collectively, our study demonstrated that the two mutations, G85R and G93A, did not have global effects in changing the SOD1 structure. Instead, the instability-associated aggregation of these mutants arose due to the local structural alterations in the edge-strands of specific beta sheets. Communicated by Ramaswamy H. Sarma